2020
DOI: 10.1186/s12880-020-00466-3
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging quantifying the severity of chronic hepatitis in rats

Abstract: Background: Diffusion tensor imaging (DTI) is mainly used for detecting white matter fiber in the brain. DTI was applied to assess fiber in liver disorders in previous studies. However, the data obtained have been insufficient in determining if DTI can be used to exactly stage chronic hepatitis. This study assessed the value of DTI for staging of liver fibrosis (F), necroinflammatory activity (A) and steatosis (S) with chronic hepatitis in rats. Methods: Seventy male Sprague-Dawley rats were divided into a con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…FA reflects the direc- Diffusion tensor magnetic resonance imaging in the grading of liver fibrosis associated with congenital ductal plate malformations e139 © Pol J Radiol 2023; 88: e135-e140 tion of water diffusion across tissue microstructure, and this depends mainly on tissue orientation [24][25][26]. Surprisingly, the literature contains studies reporting positive [27] and negative correlations [28,29] between FA and the degree of liver fibrosis. The previous heterogenicity related to FA findings could be attributed to the complex histopathological changes associated with fibrosis, such as inflammation, fatty infiltration, as well as extracellular collagen breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…FA reflects the direc- Diffusion tensor magnetic resonance imaging in the grading of liver fibrosis associated with congenital ductal plate malformations e139 © Pol J Radiol 2023; 88: e135-e140 tion of water diffusion across tissue microstructure, and this depends mainly on tissue orientation [24][25][26]. Surprisingly, the literature contains studies reporting positive [27] and negative correlations [28,29] between FA and the degree of liver fibrosis. The previous heterogenicity related to FA findings could be attributed to the complex histopathological changes associated with fibrosis, such as inflammation, fatty infiltration, as well as extracellular collagen breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies discuss the role of shear-wave elastography, magnetic resonance (MR) elastography, and MR spectroscopy in the diagnosis and monitoring of patients with AIH, but these results are preliminary and overlapping [10][11][12][13]. Diffusion tensor imaging (DTI) provides in-vivo tissue microstructure information by measuring the water diffusivity for a given voxel that can be represented by parameters such as the mean diffusivity (MD) and the fractional anisotropy (FA) [14][15][16][17][18][19][20][21]. Some studies have reported that DWI is a promising technique in the detection and quantification of hepatic inflammation and fibrosis in adults and children [22][23][24].…”
Section: Introductionmentioning
confidence: 99%